Penerapan Akuntansi Pertanggungjawaban Sosial Corporate Social Responsibility Pada PT. Tarungin Bina Mitra - Maria Anastasia; Sriyunia Anizar (Politeknik Ganesha Medan, 2022)
The purpose of this study was to determine the application of Corporate Social Responsibility (CSR) accounting at PT. Tarungin Bina Mitra, Binuang District, Tapin Regency which has been and should have been based on Law Number 40 of 2007. The method used is a qualitative analysis approach with a descriptive type. Research with qualitative analysis is research that has quality information that is disclosed in reasonable conditions or for what it is. The results showed that the implementation of corporate social responsibility was carried out by PT. Tarungin Bina Mitra, Binuang District, Tapin Regency so far, it can be seen in the financial statements in its accounting period that there is no specific application of accountability to the community (CSR), so far this company has only issued operational and general expenses for the benefit of company management such as routine activities. Breaking the fast, incidental donations, and national holiday activities that proposals, while for targeted CSR activities, is in accordance with the request of the directly affected community (people who live close to the company's location). Companies should set aside the burden of funds for social and environmental responsibility programs for the community that are useful for the good name/image of the company itself and can report its social and environmental responsibility programs in financial statements.